Worldwide research productivity in critical care medicine. - Michalopoulos, Argyris.; Bliziotis, Ioannis A.; Rizos, Michael.; Falagas, Matthew E. (2016)
Introduction: The number of publications and the impact factor of journals are accepted estimates of the quantity and quality of research productivity. The objective of the present study was to assess the worldwide scientific contribution in the field of critical care medicine.; Keywords: gross domestic product, gross national income, intensive care unit, Journal Citation Reports.; Springer Open.